Lateralization of Executive Function: Working Memory Advantage for Same Hemifield Stimuli in the Monkey - Tang, Hua; Riley, Mitchell R.; Constantinidis, Christos (Frontiers in Neuroscience, 2017)
Working memory capacity, the amount of information that may be maintained in mind over a period of seconds, is extremely limited, to a handful of items. Some evidence exists that the number of visual items that may be maintained in working memory is independent for the two hemifields. To test this idea, we trained monkeys to perform visual working memory tasks that required maintenance in memory of the locations and/or shapes of 3–5 visual stimuli. We then tested whether systematic performance differences were present for stimuli concentrated in the same hemifield, vs. distributed across hemifields. We found little evidence to support the expectation that working memory capacity is independent in the two hemifields. Instead, when an advantage of stimulus arrangement was present, it involved multiple stimuli presented in the same hemifield. This conclusion was consistent across variations of the task, performance levels, and apparent strategies adopted by individual subjects. This result suggests that factors such as grouping that favor processing of stimuli in relative proximity may counteract the benefits of independent processing in the two hemispheres. Our results reveal an important property of working memory and place constraints on models of working memory capacity.